HEALTH COMMUNICATION MESSAGE PLANNING IN INSTAGRAM - Febri Santa Nova; Isbandi Sutrisno; Kurnia Arofah (The Indonesian Journal of Communication Studies, 2020)
Health communication is interpersonal communication focused on how an individual faces health-related issues and seeks to maintain his health. The lack of awareness and public knowledge about oral health is why many clinics and illegal noneducated dental practicians in Indonesia nowadays. The emergence of an Instagram account @korbantukanggigi is one way to make the public aware and educate the public about the dangers and consequences of illegal noneducated dental practician. This research aims to determine the process of message planning on the @korbantukanggigi Instagram account about unlawful noneducated dental practicians' education. This research using the Planning Theory by Charles Berger and New Media Theory. The method used is descriptive qualitative research, collecting data through in-depth interviews, observation, and documentation. The research results in planning messages there were five stages: the report stage, discussion stage, the drafting of the statement, goals, and the success of delivering the message. In implementing the message production technique, the researchers found that the @korbantukanggigi account used the humorous appeal technique and the one-side issue in providing education. Korbantukanggigi has created opportunities for new knowledge about a dentist's world, a place to share the viewpoint of the illegal noneducated dental practician and education related to dental and oral health, which the public largely ignored.